Multi-level governance for improving air quality in cities in the UNECE region: a science policy perspective - Guus J.M. Velders; Andreas Eisold; Philippe Thunis; Gregor Kiesewetter; Martin Lutz; Rob Maas; Maaike Lammerts-Huitema; Martine Ouwersloot (Atmospheric Environment, 2026)

The Effects of Land‐Use Dynamics on Avian Phylogenetic Diversity Across Island Ecosystems - Halvina G. Saiya; David P. Edwards; Matthew J. Struebig; David J. I. Seaman; Robby Butarbutar; Nurul L. Winarni; Simon L. Mitchell; Jatna Supriatna; Rob W. Martin; Adi Karya; Robert P. Freckleton (Journal of Biogeography, 2026)
Aim To test whether forest extent and recent forest‐cover change are associated with avian phylogenetic diversity and community‐level evolutionary value across islands. Location Seven islands spanning Borneo and Wallacea in the Malay Archipelago. Taxon Terrestrial birds. Methods We sampled 1410 sites (2010–2022). We calculated phylogenetic diversity (PD), mean phylogenetic distance (MPD), mean nearest taxon distance (MNTD) and their standardised effect sizes (SES), as well as community‐level EDGE (Evolutionarily Distinct and Globally Endangered). Responses to (i) average forest proportion (250‐m radius) and (ii) recent forest‐cover change were analysed with spatial linear mixed‐effects. Results Observed PD showed a negative visual trend with increasing forest proportion, whereas SES PD declined. MPD showed only a weak positive visual trend with forest proportion, whereas SES MPD showed no clear response. Although observed MNTD appeared to increase in the binned visual summaries, both observed MNTD and SES MNTD showed significant negative associations with forest cover in the spatial models, indicating stronger nearest‐neighbour phylogenetic clustering in more forested sites. Effects of recent forest loss (2010–2022) on SES metrics were generally weak and inconsistent. Although PD also declined with decreasing rates of forest change, community‐level EDGE was higher where forest cover was greater, indicating higher average evolutionary distinctiveness and extinction risk. Main Conclusions In this archipelagic system, forest amount is a key correlate of phylogenetic structure and the retention of evolutionarily distinctive, high‐risk lineages. By contrast, recent forest‐cover change showed weaker and more context‐dependent associations. Conserving intact forests remains crucial for safeguarding the evolutionary legacy of island bird communities.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

A shallow, subduction-modified continental lithospheric mantle source for the Palaeoproterozoic Hart Dolerite, Western Australia - Alex E. Eves; Rob R. Ramsay; Anthony I.S. Kemp; Roland Maas; Laure Martin; Marco L. Fiorentini (Precambrian Research, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

From promises to action: Analyzing global commitments to tackle hunger and food insecurity - Christina Zorbas; Danielle Resnick; Eleanor Jones; Shoba Suri; Elyse Iruhiriye; Derek Headey; Will Martin; Rob Vos; Purnima Menon (Food Policy, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Impact of pollution on the temperature sensitivity of multiple Norway spruce tree-ring parameters in Central Europe - Yumei Jiang; Krešimir Begović; Martin Lexa; Juliana Nogueira; Georg von Arx; Jan Tumajer; Ryszard Kaczka; Filip Oulehle; Nataliya Korolyova; Jesper Björklund; Kristina Seftigen; Vaclav Treml; et al. (Agricultural and Forest Meteorology, 2025)

Assessing the chemical burden of the North-East Atlantic ecosystem through targeted and untargeted HRMS-based approaches - Georgios Gkotsis; Maria-Christina Nika; Nikiforos Alygizakis; Konstantinos Vasilatos; Antonia Athanasopoulou; Jonathan L. Barber; Rob Berbee; Thierry Burgeot; Susana Galante Oliveira; Johan Gustafsson; Alejandro Iglesias Campos; Ulrike Kammann; et al. (Journal of Hazardous Materials, 2025)

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Dynamics of IS 1071 and Its Accessory Gene Functions During Start‐Up of an On‐Farm Biopurification System - Jia‐Ying Wang; Vincent Dunon; Vimac Nolla Ardevol; Jérémie Béguet; Sven Jechalke; Ellen Pauwelyn; Rob Lavigne; Kornelia Smalla; Fabrice Martin‐Laurent; Dirk Springael (Environmental Microbiology, 2025)
Insertion sequences (IS) are drivers of bacterial diversification by facilitating recruitment and horizontal transfer of adaptive genes involving composite transposon structures, but their evolutionary role at the community level is rarely addressed. This study explores the dynamics of IS 1071 and the cargo of IS 1071 ‐associated putative composite transposons in the establishment of a pesticide‐degrading microbiome in an on‐farm biopurification system (BPS)—which treats pesticide‐contaminated wastewater and is considered a hotspot of microbial evolution—during the crucial start‐up phase. Pesticide mineralisation assays and quantitative PCR targeting pesticide catabolic genes showed that the microbial community, upon feeding on the pesticide‐contaminated wastewater, rapidly evolved into a pesticide‐degrading microbiome. Concomitantly, an increase in the relative abundances of several mobile genetic elements, including IS 1071 , was observed, as well as a striking enrichment of xenobiotic catabolic genes in the cargo of putative IS 1071 ‐flanked composite transposons. The IS 1071 cargo catabolic genes diversified over time and were mainly of Betaproteobacterial origin. Clear changes in community composition were observed both in the total bacterial community and the Betaproteobacterial community. We conclude that IS 1071 supports the rapid establishment of pesticide catabolism in the BPS microbiome, highlighting the contribution of IS elements to microbial community adaptation to environmental changes.

Monitoring Antarctic krill (Euphausia superba) distribution in the Southern Ocean: environmental DNA (eDNA) adds to the toolbox - Leonie Suter; Alicia Burns; Sophie Bestley; Jez Bird; Madeleine J. Brasier; Martin Cox; Derek Hamer; Olivia J. Johnson; So Kawaguchi; Rob King; Andreas Klocker; Jessica Melvin; et al. (Frontiers in Marine Science, 2025)
Antarctic krill ( Euphausia superba Dana) is a key species of the Southern Ocean ecosystem, immensely abundant and targeted by the krill fishery. For their sustainable management, krill distribution and biomass estimates are required, typically achieved through acoustic-trawl surveys. We explore how krill environmental DNA (eDNA) can contribute to our understanding or Antarctic krill habitat and distribution. We collected eDNA samples by filtering five liters of seawater per sample in the East Antarctic Southern Ocean from the surface (5 m depth) and seafloor (381–4422 m depth, total n = 110). We used quantitative PCR to measure Antarctic krill eDNA abundance and age, and eDNA metabarcoding to detect any krill species. This eDNA data was compared to acoustic, visual and trawl detections of Antarctic krill. Antarctic krill eDNA was common in surface samples and largely overlapped with visual and trawl detections. Highest eDNA concentrations were detected above krill swarms, with concentrations declining with increasing distance from swarms. Near recent eDNA sampling locations, krill swarms were more likely acoustically detected than near old eDNA sampling locations. Antarctic krill detections were less common in seafloor locations, and detections were concentrated in the continental slope area to the south of the survey area, both for visual detections and for recent eDNA detections. Both methods detected Antarctic krill at great depths (recent eDNA: 4300 m; visual: 3080 m). In both eDNA and trawl data, Antarctic krill was the dominant krill species, followed by Thysanoessa macrura G.O. Sars, which was particularly abundant in larval stages throughout the survey area, including at Antarctic krill swarm locations. We recommend the inclusion of eDNA data for Antarctic krill distribution estimates and understanding of habitat use, particularly in difficult-to-access areas, such as under ice or benthic habitats.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Migratory Birds Advance Spring Arrival and Egg‐Laying in the Arctic, Mostly by Travelling Faster - Thomas K. Lameris; Michiel P. Boom; Rascha J. M. Nuijten; Nelleke H. Buitendijk; Götz Eichhorn; Bruno J. Ens; Klaus‐Michael Exo; Petr M. Glazov; Sveinn Are Hanssen; Philip Hunke; Henk P. van der Jeugd; Margje E. de Jong; et al. (Global Change Biology, 2025)
In the current warming climate, many organisms in seasonal environments advance their timing of reproduction to benefit from resource peaks earlier in spring. For migrants, the potential to advance reproduction may be constrained by their migration strategies, notably their ability to advance arrival at the breeding grounds. Recent studies show various changes in migration strategies, including wintering closer to the breeding grounds, earlier departure from the wintering grounds or faster travels by spending less time at stopover sites. However, whether such changes lead to earlier arrival or earlier breeding remains an open question. We studied changes in migration and reproduction timing in 12 populations of nine migratory birds, including seabirds, shorebirds, birds of prey and waterfowl breeding at Arctic sites bordering the Greenland and Barents Sea, a region undergoing rapid climate warming. The timing of migration and reproduction was derived from tracking and field data and analysed to study (1) how timing has changed in response to the changing moment of snowmelt at the breeding grounds and (2) what adjustments in migration strategies this involved. We found that in years with early snowmelt, egg‐laying in multiple populations advanced, but only two waterfowl populations also advanced arrival in the Arctic. In contrast, arrival in the Arctic generally advanced with time, even when snowmelt or egg‐laying dates did not advance. Earlier arrival with time was mostly explained by populations traveling to the Arctic faster, likely spending less time at stopover sites. Inability to forecast conditions in the Arctic may limit birds to adjust migration timing to annually varying snowmelt, but we show that several species, particularly waterfowl, are able to travel faster and advance the timing of migration over the years. The question remains whether this reflects adaptations to Arctic climate change or other factors, for example, environmental changes along the migratory route.

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Advancing Patient Advocacy in Mycology: Cultivating Collaboration in Education, Research, and Policy - Rob Purdie; Rasha Kuran; Ana Alastruey-Izquierdo; Hatim Sati; Juan Luis Rodriguez-Tudela; Martin Hoenigl; John Perfect; Rita Oladele; Thomas J. Walsh; Tom Chiller (Mycopathologia, 2025)
In the healthcare landscape, diseases such as cancer and HIV/AIDS have benefited from the patient's perspective. For fungal diseases, the patient voice remains absent in critical areas such as policy formulation, funding decisions, and research priorities. Patients affected by fungal disease, along with their caregivers and advocacy groups, possess invaluable insights into the challenges and unmet needs they face. By elevating their voices and experiences, policymakers, funding agencies, and researchers can gain a more comprehensive understanding of the multifaceted nature of fungal disease and the urgency of addressing them. This paper addresses the pressing need for a coordinated effort to elevate the patient voice in advocating for improved policies, increased funding, and enhanced research initiatives regarding fungal disease.

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

AVOTREX : A Global Dataset of Extinct Birds and Their Traits - Ferran Sayol; Joseph P. Wayman; Paul Dufour; Thomas E. Martin; Julian P. Hume; Maria Wagner Jørgensen; Natàlia Martínez‐Rubio; Ariadna Sanglas; Filipa C. Soares; Rob Cooke; Chase D. Mendenhall; Jay R. Margolis; et al. (Global Ecology and Biogeography, 2024)
Motivation Human activities have been reshaping the natural world for tens of thousands of years, leading to the extinction of hundreds of bird species. Past research has provided evidence of extinction selectivity towards certain groups of species, but trait information is lacking for the majority of clades, especially for prehistoric extinctions identified only through subfossil remains. This incomplete knowledge potentially obscures the structure of natural communities, undermining our ability to infer changes in biodiversity across space and time, including trends in functional and phylogenetic diversity. Biases in currently available trait data also limit our ability to identify drivers and processes of extinction. Here we present AVOTREX, an open‐access database of species traits for all birds known to have gone extinct in the last 130,000 years. This database provides detailed morphological information for 610 extinct species, along with a pipeline to build phylogenetic trees that include these extinct species. Main Types of Variables Contained For each extinct bird species, we provide information on the taxonomy, geographic location, and period of extinction. We also present data on island endemicity, flight ability, and body mass, as well as standard measurements of external (matching the AVONET database of extant birds) and skeletal morphology from museum specimens where available. To ensure comprehensive morphological data coverage, we estimate all missing morphological measurements using a data imputation technique based on machine learning. Finally, we provide an R package to graft all extinct species onto a global phylogeny of extant species (BirdTree). Spatial Location and Grain Global. Time Period and Grain All known globally extinct bird species from 130,000 years ago up until 2024. Major Taxa and Level of Measurement Birds (Class Aves), species level. Software Format Spreadsheets (.csv) stored in Dryad.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Diurnal to interannual variability in the Northeast Atlantic from hydrographic transects and fixed time-series across the Rockall Trough - Eoghan Daly; Glenn Nolan; Alan Berry; Janina V. Büscher; Rachel R. Cave; Levke Caesar; Margot Cronin; Sheena Fennell; Kieran Lyons; Aedín McAleer; Gerard D. McCarthy; Evin McGovern; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

From reproductive behaviour to responses to predators: Ocean acidification does not impact the behaviour of an herbivorous marine gastropod - Sabine Roussel; Manon Coheleach; Sophie Martin; Rob Day; Aicha Badou; Sylvain Huchette; Philippe Dubois; Arianna Servili; Fanny Gaillard; Stéphanie Auzoux-Bordenave (Science of The Total Environment, 2024)

Knowledge gaps do not preclude extinction risk assessments: A response to Gula et al. (2023) - Alex J. Berryman; Rob W. Martin; Ian J. Burfield; Stuart H.M. Butchart (Biological Conservation, 2023)

Microbial communities associated with landfarming amendments during bioremediation of crude oil in Niger Delta soils - Paul Iturbe-Espinoza; David M. Brown; James T. Weedon; Martin Braster; Bernd W. Brandt; Matthijs Bonte; Rob J.M. van Spanning (Applied Soil Ecology, 2023)

Correlating the succession of microbial communities from Nigerian soils to petroleum biodegradation - Paul Iturbe-Espinoza; Matthijs Bonte; James T Weedon; Martin Braster; Bernd W Brandt; Rob JM van Spanning (World Journal of Microbiology and Biotechnology, 2023)
Whilst biodegradation of different hydrocarbon components has been widely demonstrated to occur by specialist oil-degrading bacteria, less is known about the impact on microbial communities as a function of oil composition by comparing the biodegradation of chemically complex fuels to synthetic products. The objectives of this study were (i) to assess the biodegradation capacity and succession of microbial communities isolated from Nigerian soils in media with crude oil or synthetic oil as sole sources of carbon and energy, and (ii) to assess the temporal variability of the microbial community size. Community profiling was done using 16 S rRNA gene amplicon sequencing (Illumina), and oil profiling using gas chromatography. The biodegradation of natural and synthetic oil differed probably due to the content of sulfur that may interfere with the biodegradation of hydrocarbons. Both alkanes and PAHs in the natural oil were biodegraded faster than in the synthetic oil. Variable community responses were observed during the degradation of alkanes and more simple aromatic compounds, but at later phases of growth they became more homogeneous. The degradation capacity and the size of the community from the more-contaminated soil were higher than those from the less-contaminated soil. Six abundant organisms isolated from the cultures were found to biodegrade oil molecules in pure cultures. Ultimately, this knowledge may contribute to a better understanding of how to improve the biodegradation of crude oil by optimizing culturing conditions through inoculation or bioaugmentation of specific bacteria during ex-situ biodegradation such as biodigesters or landfarming.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

The EnMAP imaging spectroscopy mission towards operations - Tobias Storch; Hans-Peter Honold; Sabine Chabrillat; Martin Habermeyer; Paul Tucker; Maximilian Brell; Andreas Ohndorf; Katrin Wirth; Matthias Betz; Michael Kuchler; Helmut Mühle; Emiliano Carmona; et al. (Remote Sensing of Environment, 2023)

Acceptable intakes (AIs) for 11 small molecule N-nitrosamines (NAs) - Joel P. Bercu; Melisa Masuda-Herrera; Alejandra Trejo-Martin; Priyanka Sura; Robert Jolly; Michelle Kenyon; Rob Thomas; David J. Ponting; David Snodin; Gregor Tuschl; Stephanie Simon; Kathleen De Vlieger; et al. (Regulatory Toxicology and Pharmacology, 2023)

Transferability and reproducibility of exposed air-liquid interface co-culture lung models - Hedwig M. Braakhuis; Eric R. Gremmer; Anne Bannuscher; Barbara Drasler; Sandeep Keshavan; Barbara Rothen-Rutishauser; Barbara Birk; Andreas Verlohner; Robert Landsiedel; Kirsty Meldrum; Shareen H. Doak; Martin J.D. Clift; et al. (NanoImpact, 2023)

Preclinical Considerations for Long-acting Delivery of Tenofovir Alafenamide from Subdermal Implants for HIV Pre-exposure Prophylaxis - Manjula Gunawardana; Mariana Remedios-Chan; Debbie Sanchez; Rob Fanter; Simon Webster; Paul Webster; John A. Moss; MyMy Trinh; Martin Beliveau; Christina M. Ramirez; Mark A. Marzinke; Joseph Kuo; et al. (Pharmaceutical Research, 2023)
Purpose Long-acting formulations of the potent antiretroviral prodrug tenofovir alafenamide (TAF) hold potential as biomedical HIV prevention modalities. Here, we present a rigorous comparison of three animal models, C57BL/6 J mice, beagle dogs, and merino sheep for evaluating TAF implant pharmacokinetics (PKs). Methods Implants delivering TAF over a wide range of controlled release rates were tested in vitro and in mice and dogs. Our existing PK model, supported by an intravenous (IV) dosing dog study, was adapted to analyze mechanistic aspects underlying implant TAF delivery. Results TAF in vitro release in the 0.13 to 9.8 mg d −1 range with zero order kinetics were attained. Implants with equivalent fabrication parameters released TAF in mice and sheep at rates that were not statistically different, but were 3 times higher in dogs. When two implants were placed in the same subcutaneous pocket, a two-week creep to C max was observed in dogs for systemic drug and metabolite concentrations, but not in mice. Co-modeling IV and TAF implant PK data in dogs led to an apparent TAF bioavailability of 9.6 in the single implant groups (compared to the IV group), but only 1.5 when two implants were placed in the same subcutaneous pocket. Conclusions Based on the current results, we recommend using mice and sheep, with macaques as a complementary species, for preclinical TAF implant evaluation with the caveat that our observations may be specific to the implant technology used here. Our report provides fundamental, translatable insights into multispecies TAF delivery via long-acting implants.

The complete genome assemblies of 19 insect pests of worldwide importance to agriculture - Rob King; Benjamin Buer; T.G. Emyr Davies; Eric Ganko; Marcus Guest; Keywan Hassani-Pak; David Hughes; Klaus Raming; Chris Rawlings; Martin Williamson; Andrew Crossthwaite; Ralf Nauen; et al. (Pesticide Biochemistry and Physiology, 2023)

Who decides? The governance of rewilding in Scotland ‘between the cracks’: community participation, public engagement, and partnerships - Alison Martin; Anke Fischer; Rob McMorran (Journal of Rural Studies, 2023)

Climatic controls on the survival and loss of ancient types of barley on North Atlantic Islands - Peter Martin; Terence A. Brown; Timothy S. George; Björn Gunnarson; Neil J. Loader; Paul Ross; John Wishart; Rob Wilson (Climatic Change, 2023)
For ancient types of barley at sites in the Scottish Isles, Faroes, and Iceland, we calculated minimum temperature requirements for grain production (grain production threshold, GPT) as accumulated degree days over the cropping season. Site suitability for barley from AD 1200 to 2000 was investigated by comparing these thresholds with reconstructions of annual cropping season degree days (CSDD) using temperature and tree-ring data. In Iceland, between AD 1200 and 1500, reconstructed CSDD were more favorable in the southwest (Reykjavik), with fewer years below the GPT, than in the North, East and West, but there were two periods (1340–1389 and 1426–1475) with low average CSDD and several years below the GPT which possibly influenced the abandonment of barley cultivation around this time. Reconstructed CSDD for the Faroes (Tórshavn) had only one year below the GPT, but 15 periods of four or more consecutive years with low CSDD which would have challenged barley cultivation, especially in the thirteenth century. Reconstructed CSDD were highest for the Scottish Isles, allowing a more prominent role of barley in the farming system and economy. Nevertheless, years with poor harvests or famines were common and about half were associated with low CSDD, resulting in a significant temperature link but also demonstrating the important contribution of other factors. Despite frequent unfavorable years in both the Faroes and Scottish Isles, resilient production systems, well-adapted barley strains and socio-economic factors allowed barley cultivation to continue, and some ancient types to survive to the present day.

Enhancing the review process in global environmental assessments: The case of the IPCC - Jean P. Palutikof; Sarah L. Boulter; Christopher B. Field; Katharine J. Mach; Martin R. Manning; Michael D. Mastrandrea; Leo Meyer; Jan C. Minx; Joy J. Pereira; Gian-Kasper Plattner; Suzana Kahn Ribeiro; Youba Sokona; et al. (Environmental Science & Policy, 2023)

Supporting the Next Generation of Leaders in the Geosciences: Barnard’s Environmental Science Pathways Scholar Program - Logan Brenner; Brian Mailloux; Sedelia Rodriguez; Terryanne Maenza-Gmelch; Elizabeth Cook; Fatima Koli; Christine Marizzi; Rob Frawley; Batoul Saad; Martin Stute (Oceanography, 2023)
To address the national need to diversify the geosciences, we created the cohort-based Environmental Science Pathways Scholars Program, or E(SP)2, for undergraduates in the Environmental Science Department at Barnard College who identify as Black, Indigenous, and people of color (BIPOC), first generation, or low income. By fostering a more inclusive community in the particularly formative stages of academic and early professional development, E(SP)2 aims to support and retain a diverse cohort of students who have developed confidence in their scientific skills and identities, and who share a passion for environmental science. E(SP)2 is modeled on the Science Pathways Scholar Program [(SP)2] at Barnard College, an active and successful multidisciplinary opportunity at Barnard College.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Correction to: Current evidence on the impact of medication optimization or pharmacological interventions on frailty or aspects of frailty: a systematic review of randomized controlled trials - Farhad Pazan; Mirko Petrovic; Antonio Cherubini; Graziano Onder; Alfonso J. Cruz-Jentoft; Michael Denkinger; Tischa J. M. van der Cammen; Jennifer M. Stevenson; Kinda Ibrahim; Chakravarthi Rajkumar; Marit Stordal Bakken; Jean-Pierre Baeyens; et al. (European Journal of Clinical Pharmacology, 2021)

Effects of DNA preservation solution and DNA extraction methods on microbial community profiling of soil - Paul Iturbe-Espinoza; Bernd W. Brandt; Martin Braster; Matthijs Bonte; David M. Brown; Rob J. M. van Spanning (Folia Microbiologica, 2021)
Microbial community profiling using high-throughput sequencing relies in part on the preservation of the DNA and the effectiveness of the DNA extraction method. This study aimed at understanding to what extent these parameters affect the profiling. We obtained samples treated with and without a preservation solution. Also, we compared DNA extraction kits from Qiagen and Zymo-Research. The types of samples were defined strains, both as single species and mixtures, as well as undefined indigenous microbial communities from soil. We show that the use of a preservation solution resulted in substantial changes in the 16S rRNA gene profiles either due to an overrepresentation of Gram-positive bacteria or to an underrepresentation of Gram-negative bacteria. In addition, 16S rRNA gene profiles were substantially different depending on the type of kit that was used for extraction. The kit from Zymo extracted DNA from different types of bacteria in roughly equal amounts. In contrast, the kit from Qiagen preferentially extracted DNA from Gram-negative bacteria while DNA from Gram-positive bacteria was extracted less effectively. These differences in kit performance strongly influenced the interpretation of our microbial ecology studies.

Correction to: Authors’ Reply to Letter to the Editor: Continued improvement to genetic diversity indicator for CBD - Linda Laikre; Paul A. Hohenlohe; Fred W. Allendorf; Laura D. Bertola; Martin F. Breed; Michael W. Bruford; W. Chris Funk; Gonzalo Gajardo; Antonio González-Rodríguez; Catherine E. Grueber; Philip W. Hedrick; Myriam Heuertz; et al. (Conservation Genetics, 2021)
A correction to this paper has been published: https://doi.org/10.1007/s10592-021-01376-9

Authors’ Reply to Letter to the Editor: Continued improvement to genetic diversity indicator for CBD - Linda Laikre; Paul A. Hohenlohe; Fred W. Allendorf; Laura D. Bertola; Martin F. Breed; Michael W. Bruford; W. Chris Funk; Gonzalo Gajardo; Antonio González-Rodríguez; Catherine E. Grueber; Philip W. Hedrick; Myriam Heuertz; et al. (Conservation Genetics, 2021)

A novel methoxydotrophic metabolism discovered in the hyperthermophilic archaeon Archaeoglobus fulgidus - Cornelia U. Welte; Rob de Graaf; Paula Dalcin Martins; Robert S. Jansen; Mike S. M. Jetten; Julia M. Kurth (Environmental Microbiology, 2021)
Summary Methoxylated aromatic compounds (MACs) are important components of lignin found in significant amounts in the subsurface. Recently, the methanogenic archaeon Methermicoccus shengliensis was shown to be able to use a variety of MACs during methoxydotrophic growth. After a molecular survey, we found that the hyperthermophilic non‐methanogenic archaeon Archaeoglobus fulgidus also encodes genes for a bacterial‐like demethoxylation system. In this study, we performed growth and metabolite analysis, and used transcriptomics to investigate the response of A. fulgidus during growth on MACs in comparison to growth on lactate. We observed that A. fulgidus converts MACs to their hydroxylated derivatives with CO 2 as the main product and sulfate as electron acceptor. Furthermore, we could show that MACs improve the growth of A. fulgidus in the presence of organic substrates such as lactate. We also found evidence that other archaea such as Bathyarchaeota, Lokiarchaeota, Verstraetearchaeota, Korarchaeota, Helarchaeota and Nezhaarchaeota encode a demethoxylation system. In summary, we here describe the first non‐methanogenic archaeon with the ability to grow on MACs indicating that methoxydotrophic archaea might play a so far underestimated role in the global carbon cycle.

Current evidence on the impact of medication optimization or pharmacological interventions on frailty or aspects of frailty: a systematic review of randomized controlled trials - Farhad Pazan; Mirko Petrovic; Antonio Cherubini; Graziano Onder; Alfonso J. Cruz-Jentoft; Michael Denkinger; Tischa J. M. van der Cammen; Jennifer M. Stevenson; Kinda Ibrahim; Chakravarthi Rajkumar; Marit Stordal Bakken; Jean-Pierre Baeyens; et al. (European Journal of Clinical Pharmacology, 2021)
Background Frailty and adverse drug effects are linked in the fact that polypharmacy is correlated with the severity of frailty; however, a causal relation has not been proven in older people with clinically manifest frailty. Methods A literature search was performed in Medline to detect prospective randomized controlled trials (RCTs) testing the effects of pharmacological interventions or medication optimization in older frail adults on comprehensive frailty scores or partial aspects of frailty that were published from January 1998 to October 2019. Results Twenty-five studies were identified, 4 on comprehensive frailty scores and 21 on aspects of frailty. Two trials on comprehensive frailty scores showed positive results on frailty although the contribution of medication review in a multidimensional approach was unclear. In the studies on aspects related to frailty, ten individual drug interventions showed improvement in physical performance, muscle strength or body composition utilizing alfacalcidol, teriparatide, piroxicam, testosterone, recombinant human chorionic gonadotropin, or capromorelin. There were no studies examining negative effects of drugs on frailty. Conclusion So far, data on a causal relationship between drugs and frailty are inconclusive or related to single-drug interventions on partial aspects of frailty. There is a clear need for RCTs on this topic that should be based on a comprehensive, internationally consistent and thus reproducible concept of frailty assessment.

Buffering effects of soil seed banks on plant community composition in response to land use and climate - Jan Plue; Hans Van Calster; Inger Auestad; Sofía Basto; Renée M. Bekker; Hans Henrik Bruun; Richard Chevalier; Guillaume Decocq; Ulf Grandin; Martin Hermy; Hans Jacquemyn; Anna Jakobsson; et al. (Global Ecology and Biogeography, 2021)
Aim Climate and land use are key determinants of biodiversity, with past and ongoing changes posing serious threats to global ecosystems. Unlike most other organism groups, plant species can possess dormant life‐history stages such as soil seed banks, which may help plant communities to resist or at least postpone the detrimental impact of global changes. This study investigates the potential for soil seed banks to achieve this. Location Europe. Time period 1978–2014. Major taxa studied Flowering plants. Methods Using a space‐for‐time/warming approach, we study plant species richness and composition in the herb layer and the soil seed bank in 2,796 community plots from 54 datasets in managed grasslands, forests and intermediate, successional habitats across a climate gradient. Results Soil seed banks held more species than the herb layer, being compositionally similar across habitats. Species richness was lower in forests and successional habitats compared to grasslands, with annual temperature range more important than mean annual temperature for determining richness. Climate and land‐use effects were generally less pronounced when plant community richness included seed bank species richness, while there was no clear effect of land use and climate on compositional similarity between the seed bank and the herb layer. Main conclusions High seed bank diversity and compositional similarity between the herb layer and seed bank plant communities may provide a potentially important functional buffer against the impact of ongoing environmental changes on plant communities. This capacity could, however, be threatened by climate warming. Dormant life‐history stages can therefore be important sources of diversity in changing environments, potentially underpinning already observed time‐lags in plant community responses to global change. However, as soil seed banks themselves appear, albeit less, vulnerable to the same changes, their potential to buffer change can only be temporary, and major community shifts may still be expected.

Beyond ecosystem modeling: A roadmap to community cyberinfrastructure for ecological data‐model integration - Istem Fer; Anthony K. Gardella; Alexey N. Shiklomanov; Eleanor E. Campbell; Elizabeth M. Cowdery; Martin G. De Kauwe; Ankur Desai; Matthew J. Duveneck; Joshua B. Fisher; Katherine D. Haynes; Forrest M. Hoffman; Miriam R. Johnston; et al. (Global Change Biology, 2021)
In an era of rapid global change, our ability to understand and predict Earth's natural systems is lagging behind our ability to monitor and measure changes in the biosphere. Bottlenecks to informing models with observations have reduced our capacity to fully exploit the growing volume and variety of available data. Here, we take a critical look at the information infrastructure that connects ecosystem modeling and measurement efforts, and propose a roadmap to community cyberinfrastructure development that can reduce the divisions between empirical research and modeling and accelerate the pace of discovery. A new era of data‐model integration requires investment in accessible, scalable, and transparent tools that integrate the expertise of the whole community, including both modelers and empiricists. This roadmap focuses on five key opportunities for community tools: the underlying foundations of community cyberinfrastructure; data ingest; calibration of models to data; model‐data benchmarking; and data assimilation and ecological forecasting. This community‐driven approach is a key to meeting the pressing needs of science and society in the 21st century.

Pharmacokinetics and pharmacodynamics of intranasal remimazolam—a randomized controlled clinical trial - Marija Pesic; Frank Schippers; Rob Saunders; Lyn Webster; Martin Donsbach; Thomas Stoehr (European Journal of Clinical Pharmacology, 2020)
Purpose Remimazolam is a novel and ultra-short-acting sedative currently developed for intravenous use in procedural sedation, general anesthesia, and ICU sedation. However, intravenous administration is not always appropriate, depending on the patient or setting. This study evaluated intranasal administration as a potential alternative route. Methods The study used a randomized, double-blind, 9 period cross-over design to compare the pharmacokinetics, pharmacodynamics, and safety of single intranasal doses of 10, 20, and 40 mg remimazolam (as powder or solution) with intranasal placebo and 4 mg intravenous remimazolam. Results Intranasal remimazolam powder had a consistent absolute bioavailability of approximately 50%; T max was 10 min; AUC and C max were dose-proportional. The higher doses of intranasal solution, however, resulted in decreasing bioavailability and loss of dose-proportionality in AUC and C max despite complete drug absorption due to partial swallowing of dose and the resulting first-pass effect. Pharmacodynamics were generally consistent with PK. Peak effects (drowsiness, relaxation, any, memory, response time) were in similar ranges after intranasal (10 to 40 mg) as intravenous (4 mg) dosing and were partially, but not consistently, dose-related. Safety results were generally consistent with other benzodiazepines; however, intranasal remimazolam (but not placebo) caused nasal discomfort/pain, in some cases even severe. Conclusions Intranasal administration of remimazolam was safe and caused sedative effects. However, the severe pain and discomfort caused by intranasal remimazolam prohibit its use by this route of administration, at least with the currently available intravenous formulation.

Community volunteer assessment of recreational water quality in the Hutt River, Wellington - Amanda E. Valois; Juliet R. Milne; Mark W. Heath; Rob J. Davies‐Colley; Emily Martin; Rebecca Stott (New Zealand Journal of Marine and Freshwater Research, 2020)
Water is an important component of many recreational opportunities and New Zealand invests significant resources in recreational water quality (RWQ) monitoring to assess risks to public health. However, monitoring primarily focuses on microbiological hazards and RWQ is considerably broader than this. The goal of this study was to take a comprehensive approach to evaluating RWQ while exploring the potential for greater public involvement in monitoring. A popular river swimming site was co‐monitored weekly by volunteers and a council field officer. The attributes monitored–water temperature, visual clarity, benthic cyanobacteria and filamentous periphyton cover, E. coli and rubbish–were identified from a volunteer workshop. There was good concordance between volunteer and council data suggesting that volunteer measurements can be considered reliable. This highlights the potential for volunteers, with professional support, including training and quality assurance, to extend council RWQ surveillance to additional monitoring sites while improving public engagement on water management.

Overhauling Ocean Spatial Planning to Improve Marine Megafauna Conservation - Ana Micaela Martins Sequeira; Graeme Clive Hays; David W. Sims; Víctor M. Eguíluz; Jorge P. Rodríguez; Michelle R. Heupel; Rob Harcourt; Hannah Calich; Nuno Queiroz; Daniel Paul Costa; Juan Fernández-Gracia; Luciana C. Ferreira; et al. (Frontiers in Marine Science, 2019)

Animal-Borne Telemetry: An Integral Component of the Ocean Observing Toolkit - Rob Harcourt; Ana M. M. Sequeira; Xuelei Zhang; Fabien Roquet; Kosei Komatsu; Michelle Heupel; Clive McMahon; Fred Whoriskey; Mark Meekan; Gemma Carroll; Stephanie Brodie; Colin Simpfendorfer; et al. (Frontiers in Marine Science, 2019)

Correction to: Resolving taxonomic uncertainty in vulnerable elasmobranchs: are the Madeira skate (Raja maderensis) and the thornback ray (Raja clavata) distinct species? - Rachel E. Ball; Barbara Serra-Pereira; Jim Ellis; Martin J. Genner; Samuel Iglésias; Andrew F. Johnson; Catherine S. Jones; Rob Leslie; Jennifer Lewis; Stefano Mariani; Gui Menezes; Francis Neat; et al. (Conservation Genetics, 2019)

Future Directions in Conservation Research on Petrels and Shearwaters - Airam Rodríguez; José M. Arcos; Vincent Bretagnolle; Maria P. Dias; Nick D. Holmes; Maite Louzao; Jennifer Provencher; André F. Raine; Francisco Ramírez; Beneharo Rodríguez; Robert A. Ronconi; Rebecca S. Taylor; et al. (Frontiers in Marine Science, 2019)

Alphasatellitidae: a new family with two subfamilies for the classification of geminivirus- and nanovirus-associated alphasatellites - Rob W. Briddon; Darren P. Martin; Philippe Roumagnac; Jesús Navas-Castillo; Elvira Fiallo-Olivé; Enrique Moriones; Jean-Michel Lett; F. Murilo Zerbini; Arvind Varsani (Archives of Virology, 2018)

Petrology and geochemistry of the 2014–2015 Holuhraun eruption, central Iceland: compositional and mineralogical characteristics, temporal variability and magma storage - Sæmundur A. Halldórsson; Enikő Bali; Margaret E. Hartley; David A. Neave; David W. Peate; Guðmundur H. Guðfinnsson; Ilya Bindeman; Martin J. Whitehouse; Morten S. Riishuus; Gro B. M. Pedersen; Sigurður Jakobsson; Rob Askew; et al. (Contributions to Mineralogy and Petrology, 2018)

My land? Your land? Scotland?—understanding sectoral similarities and differences in Scottish land use visions - Christiane Valluri-Nitsch; Marc J. Metzger; Rob McMorran; Martin F. Price (Regional Environmental Change, 2018)

The biogeographical history of the interaction between mycoheterotrophic Thismia (Thismiaceae) plants and mycorrhizal Rhizophagus (Glomeraceae) fungi - Vincent S. F. T. Merckx; Sofia I. F. Gomes; Mark Wapstra; Colin Hunt; Greg Steenbeeke; Constantijn B. Mennes; Neville Walsh; Rob Smissen; Tsung‐Hsin Hsieh; Erik F. Smets; Martin I. Bidartondo (Journal of Biogeography, 2017)
Aim Achlorophyllous mycoheterotrophic plants and mycorrhizal fungi often have highly specific interactions that potentially limit the plants’ distribution and diversification potential. However, specificity in biotic interactions may differ considerably over a species’ distribution range and therefore interactions need to be studied over their entire range to assess their evolution in space and time. The present study investigates the biogeographical history of the interaction between five closely related mycoheterotrophic Thismia species and arbuscular mycorrhizal fungi over the distribution range of the plant species. Location Temperate south‐east Australia and New Zealand. Methods Phylogenetic relationships of Thismia (nr ITS and mt cob ) and their arbuscular mycorrhizal fungi (partial nr SSU ) were reconstructed based on data from 65 plant specimens. The diversification times in Thismia were estimated with a Bayesian relaxed clock approach using a Dioscoreales framework (nr SSU , mt atp1 , mt matR , mt nad1 b‐c ). Ancestral geographical ranges were reconstructed using a maximum likelihood approach. The same approach was used to reconstruct ancestral mycorrhizal associations. Results Our analysis shows that Thismia plants have highly specific, phylogenetically conserved and evolutionarily persistent interactions with Rhizophagus fungi. Nevertheless, Thismia was able to diversify and radiate recently due to the wide geographical distribution of the host fungi. In addition, we find that although the mycorrhizal interactions of this clade of mycoheterotrophs are strictly bound to a fungal lineage, host switches remain possible. Main conclusions In this clade of closely related mycoheterotrophs, dependency on highly specific fungal interactions is the result of phylogenetic niche conservatism, acting over at least 12 million years. Nevertheless, plants that are dependent on highly specific fungal interactions have ample opportunities to disperse and radiate over the geographical range of their hosts. Our study highlights the need to link the ecology and evolution of species interactions over broad geographical and evolutionary scales for understanding mycorrhizal interactions.

A primer on systematic reviews in toxicology - Sebastian Hoffmann; Rob B. M. de Vries; Martin L. Stephens; Nancy B. Beck; Hubert A. A. M. Dirven; John R. Fowle; Julie E. Goodman; Thomas Hartung; Ian Kimber; Manoj M. Lalu; Kristina Thayer; Paul Whaley; et al. (Archives of Toxicology, 2017)

Capulavirus and Grablovirus: two new genera in the family Geminiviridae - Arvind Varsani; Philippe Roumagnac; Marc Fuchs; Jesús Navas-Castillo; Enrique Moriones; Ali Idris; Rob W. Briddon; Rafael Rivera-Bustamante; F. Murilo Zerbini; Darren P Martin (Archives of Virology, 2017)

Landscape genetics structure of European sweet chestnut (Castanea sativa Mill): indications for conservation priorities - Claudia Mattioni; M. Angela Martin; Francesca Chiocchini; Marcello Cherubini; Muriel Gaudet; Paola Pollegioni; Ivaylo Velichkov; Rob Jarman; Frank M. Chambers; Ladislave Paule; Vasilica L. Damian; Ghiţă C. Crainic; et al. (Tree Genetics & Genomes, 2017)

Truncation of the MSH2 C-terminal 60 amino acids disrupts effective DNA mismatch repair and is causative for Lynch syndrome - Eva Wielders; Elly Delzenne-Goette; Rob Dekker; Martin van der Valk; Hein te Riele (Familial Cancer, 2017)

A global database of ant species abundances - Heloise Gibb; Rob R. Dunn; Nathan J. Sanders; Blair F. Grossman; Manoli Photakis; Silvia Abril; Donat Agosti; Alan N. Andersen; Elena Angulo; Inge Armbrecht; Xavier Arnan; Fabricio B. Baccaro; et al. (Ecology, 2017)
What forces structure ecological assemblages? A key limitation to general insights about assemblage structure is the availability of data that are collected at a small spatial grain (local assemblages) and a large spatial extent (global coverage). Here, we present published and unpublished data from 51 ,388 ant abundance and occurrence records of more than 2,693 species and 7,953 morphospecies from local assemblages collected at 4,212 locations around the world. Ants were selected because they are diverse and abundant globally, comprise a large fraction of animal biomass in most terrestrial communities, and are key contributors to a range of ecosystem functions. Data were collected between 1949 and 2014, and include, for each geo‐referenced sampling site, both the identity of the ants collected and details of sampling design, habitat type, and degree of disturbance. The aim of compiling this data set was to provide comprehensive species abundance data in order to test relationships between assemblage structure and environmental and biogeographic factors. Data were collected using a variety of standardized methods, such as pitfall and Winkler traps, and will be valuable for studies investigating large‐scale forces structuring local assemblages. Understanding such relationships is particularly critical under current rates of global change. We encourage authors holding additional data on systematically collected ant assemblages, especially those in dry and cold, and remote areas, to contact us and contribute their data to this growing data set.

Resolving taxonomic uncertainty in vulnerable elasmobranchs: are the Madeira skate (Raja maderensis) and the thornback ray (Raja clavata) distinct species? - Rachel E. Ball; Barbara Serra-Pereira; Jim Ellis; Martin J. Genner; Samuel Iglésias; Andrew F. Johnson; Catherine S. Jones; Rob Leslie; Jennifer Lewis; Stefano Mariani; Gui Menezes; Francis Neat; et al. (Conservation Genetics, 2016)
Skates and rays constitute the most speciose group of chondrichthyan fishes, yet are characterised by remarkable levels of morphological and ecological conservatism. They can be challenging to identify, which makes monitoring species compositions for fisheries management purposes problematic. Owing to their slow growth and low fecundity, skates are vulnerable to exploitation and species exhibiting endemism or limited ranges are considered to be the most at risk. The Madeira skate Raja maderensis is endemic and classified as ‘Data Deficient’ by the IUCN, yet its taxonomic distinctiveness from the morphologically similar and more wide-ranging thornback ray Raja clavata is unresolved. This study evaluated the sequence divergence of both the variable control region and cytochrome oxidase I ‘DNA barcode’ gene of the mitochondrial genome to elucidate the genetic differentiation of specimens identified as R. maderensis and R. clavata collected across much of their geographic ranges. Genetic evidence was insufficient to support the different species designations. However regardless of putative species identification, individuals occupying waters around the Azores and North African Seamounts represent an evolutionarily significant unit worthy of special consideration for conservation management.

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Inheritance of resistance to cassava green mite and other useful agronomic traits in cassava grown in Zambia - Able Chalwe; Rob Melis; Paul Shanahan; Martin Chiona (Euphytica, 2015)

The impact of chronic endurance and resistance training upon the right ventricular phenotype in male athletes - Victor Utomi; David Oxborough; Euan Ashley; Rachel Lord; Sarah Fletcher; Mike Stembridge; Rob Shave; Martin D. Hoffman; Greg Whyte; John Somauroo; Sanjay Sharma; Keith George (European Journal of Applied Physiology, 2015)

Quality and Safety Requirements for Sustainable Phage Therapy Products - Jean-Paul Pirnay; Bob G. Blasdel; Laurent Bretaudeau; Angus Buckling; Nina Chanishvili; Jason R. Clark; Sofia Corte-Real; Laurent Debarbieux; Alain Dublanchet; Daniel De Vos; Jérôme Gabard; Miguel Garcia; et al. (Pharmaceutical Research, 2015)

Revision of Begomovirus taxonomy based on pairwise sequence comparisons - Judith K. Brown; F. Murilo Zerbini; Jesús Navas-Castillo; Enrique Moriones; Roberto Ramos-Sobrinho; José C. F. Silva; Elvira Fiallo-Olivé; Rob W. Briddon; Cecilia Hernández-Zepeda; Ali Idris; V. G. Malathi; Darren P. Martin; et al. (Archives of Virology, 2015)

Metabolite profiling and peptidoglycan analysis of transient cell wall‐deficient bacteria in a new E scherichia coli model system - Alexander Cambré; Michael Zimmermann; Uwe Sauer; Bram Vivijs; William Cenens; Chris W. Michiels; Abram Aertsen; Martin J. Loessner; Jean‐Paul Noben; Juan A. Ayala; Rob Lavigne; Yves Briers (Environmental Microbiology, 2015)
Summary Many bacteria are able to assume a transient cell wall‐deficient (or L ‐form) state under favourable osmotic conditions. Cell wall stress such as exposure to β‐lactam antibiotics can enforce the transition to and maintenance of this state. L ‐forms actively proliferate and can return to the walled state upon removal of the inducing agent. We have adopted E scherichia coli as a model system for the controlled transition to and reversion from the L ‐form state, and have studied these dynamics with genetics, cell biology and ‘omics’ technologies. As such, a transposon mutagenesis screen underscored the requirement for the R cs phosphorelay and colanic acid synthesis, while proteomics show only little differences between rods and L ‐forms. In contrast, metabolome comparison reveals the high abundance of lysophospholipids and phospholipids with unsaturated or cyclopropanized fatty acids in E . coli L ‐forms. This increase of membrane lipids associated with increased membrane fluidity may facilitate proliferation through bud formation. Visualization of the residual peptidoglycan with a fluorescently labelled peptidoglycan binding protein indicates de novo cell wall synthesis and a role for septal peptidoglycan synthesis during bud constriction. The DD ‐carboxypeptidases PBP5 and PBP6 are threefold and fourfold upregulated in L ‐forms, indicating a specific role for regulation of crosslinking during L ‐form proliferation.

Identification of an Australian-like dicot-infecting mastrevirus in Pakistan - Simona Kraberger; Huma Mumtaz; Sohini Claverie; Darren P. Martin; Rob W. Briddon; Arvind Varsani (Archives of Virology, 2015)

The right ventricle following ultra-endurance exercise: insights from novel echocardiography and 12-lead electrocardiography - Rachel Lord; John Somauroo; Mike Stembridge; Nikhil Jain; Martin D. Hoffman; Keith George; Helen Jones; Rob Shave; Francois Haddad; Euan Ashley; David Oxborough (European Journal of Applied Physiology, 2015)

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

Foraging behaviour and habitat use of chick-rearing Australasian Gannets in New Zealand - Gabriel E. Machovsky-Capuska; Mark E. Hauber; Mariela Dassis; Eric Libby; Martin C. Wikelski; Rob Schuckard; David S. Melville; Willie Cook; Michelle Houston; David Raubenheimer (Journal of Ornithology, 2014)

Visual and linguistic cues to graspable objects - Andriy Myachykov; Rob Ellis; Angelo Cangelosi; Martin H. Fischer (Experimental Brain Research, 2013)

A genome-wide pairwise-identity-based proposal for the classification of viruses in the genus Mastrevirus (family Geminiviridae) - Brejnev Muhire; Darren P. Martin; Judith K. Brown; Jesús Navas-Castillo; Enrique Moriones; F. Murilo Zerbini; Rafael Rivera-Bustamante; V. G. Malathi; Rob W. Briddon; Arvind Varsani (Archives of Virology, 2013)

A genomic island linked to ecotype divergence in A tlantic cod - Jakob Hemmer‐Hansen; Einar E. Nielsen; Nina O. Therkildsen; Martin I. Taylor; Rob Ogden; Audrey J. Geffen; Dorte Bekkevold; Sarah Helyar; Christophe Pampoulie; Torild Johansen; Gary R. Carvalho (Molecular Ecology, 2013)
The genomic architecture underlying ecological divergence and ecological speciation with gene flow is still largely unknown for most organisms. One central question is whether divergence is genome‐wide or localized in ‘genomic mosaics’ during early stages when gene flow is still pronounced. Empirical work has so far been limited, and the relative impacts of gene flow and natural selection on genomic patterns have not been fully explored. Here, we use ecotypes of Atlantic cod to investigate genomic patterns of diversity and population differentiation in a natural system characterized by high gene flow and large effective population sizes, properties which theoretically could restrict divergence in local genomic regions. We identify a genomic region of strong population differentiation, extending over approximately 20 cM, between pairs of migratory and stationary ecotypes examined at two different localities. Furthermore, the region is characterized by markedly reduced levels of genetic diversity in migratory ecotype samples. The results highlight the genomic region, or ‘genomic island’, as potentially associated with ecological divergence and suggest the involvement of a selective sweep. Finally, we also confirm earlier findings of localized genomic differentiation in three other linkage groups associated with divergence among eastern A tlantic populations. Thus, although the underlying mechanisms are still unknown, the results suggest that ‘genomic mosaics’ of differentiation may even be found under high levels of gene flow and that marine fishes may provide insightful model systems for studying and identifying initial targets of selection during ecological divergence.

Corrigendum - Morten T. Limborg; Sarah J. Helyar; Mark de Bruyn; Martin I. Taylor; Einar E. Nielsen; Rob Ogden; Gary R. Carvalho; Dorte Bekkevold (Molecular Ecology, 2013)

Genetic inheritance of resistance to cowpea aphid-borne mosaic virus in cowpea - Martin Orawu; Rob Melis; Mark Laing; John Derera (Euphytica, 2013)
Cowpea aphid-borne mosaic virus (CABMV) is a major virus disease in Uganda that causes substantial loss of the cowpea crop especially in growth and yield. The mode of gene action conferring resistance to the virus is not well understood. The objective of the study was to determine the genetic inheritance of resistance in cowpea crosses. Three susceptible (S) cowpea landraces that are commonly grown by farmers were crossed with five introduced resistant cowpea varieties in accordance with a North Carolina mating design II scheme. The F 1 , F 2 and BC 1 F 1 progenies generated were evaluated in the field together with their parents. They were then infected with two infection methods namely: by spreader-rows of S cultivar (Ebelat) and artificial inoculation of virus extracts. The results obtained showed that general combining ability (GCA) and specific combining ability (SCA) effects were significant, indicating that both additive and non-additive gene effects controlled virus infection. The results further demonstrated that the GCA effects (59.8 %) were more important than SCA effects (40.2 %) in determining virus resistance in the cowpea varieties. Utilisation of good general combiners of the varieties MU-93, IT82D-516-2, SECOW-2W and IT85F-2841 in hybridisation to improve virus resistance in cowpea crosses would be recommended. The result of this study provided an indication that CABMV resistance was conditioned by more than one recessive gene in eight populations, but also revealed resistance to be conditioned by a single recessive gene in the other seven populations. Observation of continuous distribution of progenies for severity data in the F 2 populations also confirmed significance of quantitative inheritance for CABMV resistance. Therefore, the significance of GCA effects suggests that recurrent selection could be applied to accumulate the additive genes for resistance in F 2 populations.

Object affordance influences instruction span - Jens K. Apel; Angelo Cangelosi; Rob Ellis; Jeremy Goslin; Martin H. Fischer (Experimental Brain Research, 2012)

Environmental selection on transcriptome‐derived SNPs in a high gene flow marine fish, the Atlantic herring ( Clupea harengus ) - MORTEN T. LIMBORG; SARAH J. HELYAR; MARK De BRUYN; MARTIN I. TAYLOR; EINAR E. NIELSEN; ROB OGDEN; GARY R. CARVALHO; DORTE BEKKEVOLD (Molecular Ecology, 2012)
High gene flow is considered the norm for most marine organisms and is expected to limit their ability to adapt to local environments. Few studies have directly compared the patterns of differentiation at neutral and selected gene loci in marine organisms. We analysed a transcriptome‐derived panel of 281 SNPs in Atlantic herring ( Clupea harengus ), a highly migratory small pelagic fish, for elucidating neutral and selected genetic variation among populations and to identify candidate genes for environmental adaptation. We analysed 607 individuals from 18 spawning locations in the northeast Atlantic, including two temperature clines (5–12 °C) and two salinity clines (5–35‰). By combining genome scan and landscape genetic analyses, four genetically distinct groups of herring were identified: Baltic Sea, Baltic–North Sea transition area, North Sea/British Isles and North Atlantic; notably, samples exhibited divergent clustering patterns for neutral and selected loci. We found statistically strong evidence for divergent selection at 16 outlier loci on a global scale, and significant correlations with temperature and salinity at nine loci. On regional scales, we identified two outlier loci with parallel patterns across temperature clines and five loci associated with temperature in the North Sea/North Atlantic. Likewise, we found seven replicated outliers, of which five were significantly associated with low salinity across both salinity clines. Our results reveal a complex pattern of varying spatial genetic variation among outlier loci, likely reflecting adaptations to local environments. In addition to disclosing the fine scale of local adaptation in a highly vagile species, our data emphasize the need to preserve functionally important biodiversity.

Population genetic structure of protected allis shad (Alosa alosa) and twaite shad (Alosa fallax) - Marc T. Jolly; Miran W. Aprahamian; Stephen J. Hawkins; Peter A. Henderson; Rob Hillman; Niall O’Maoiléidigh; Peter S. Maitland; Rayner Piper; Martin J. Genner (Marine Biology, 2012)

Attention deployment during memorizing and executing complex instructions - Jens K. Apel; Gavin F. Revie; Angelo Cangelosi; Rob Ellis; Jeremy Goslin; Martin H. Fischer (Experimental Brain Research, 2011)

Mitochondrial DNA sequence variation in spiny lobsters: population expansion, panmixia, and divergence - Eugenia Naro-Maciel; Brendan Reid; Katherine E. Holmes; Daniel R. Brumbaugh; Meredith Martin; Rob DeSalle (Marine Biology, 2011)

Recombination patterns in dicot-infecting mastreviruses mirror those found in monocot-infecting mastreviruses - Darren P. Martin; Rob W. Briddon; Arvind Varsani (Archives of Virology, 2011)

Analysis of the sequence of a dicot-infecting mastrevirus (family Geminiviridae) originating from Syria - Huma Mumtaz; Safaa G. Kumari; Shahid Mansoor; Darren P. Martin; Rob W. Briddon (Virus Genes, 2011)

The Phage Therapy Paradigm: Prêt-à-Porter or Sur-mesure? - Jean-Paul Pirnay; Daniel De Vos; Gilbert Verbeken; Maia Merabishvili; Nina Chanishvili; Mario Vaneechoutte; Martin Zizi; Geert Laire; Rob Lavigne; Isabelle Huys; Guy Van den Mooter; Angus Buckling; et al. (Pharmaceutical Research, 2011)

Bromus catharticus striate mosaic virus: a new mastrevirus infecting Bromus catharticus from Australia - James Hadfield; Darren P. Martin; Daisy Stainton; Simona Kraberger; Betty E. Owor; Dionne N. Shepherd; Francisco Lakay; Peter G. Markham; Ray S. Greber; Rob W. Briddon; Arvind Varsani (Archives of Virology, 2011)

The SPO1-related bacteriophages - Jochen Klumpp; Rob Lavigne; Martin J. Loessner; Hans-Wolfgang Ackermann (Archives of Virology, 2010)

Research needs for incorporating the ecosystem service approach into EU biodiversity conservation policy - Christian Anton; Juliette Young; Paula A. Harrison; Martin Musche; Györgyi Bela; Christian K. Feld; Richard Harrington; John R. Haslett; György Pataki; Mark D. A. Rounsevell; Michalis Skourtos; J. Paulo Sousa; et al. (Biodiversity and Conservation, 2010)

Changing conservation strategies in Europe: a framework integrating ecosystem services and dynamics - John R. Haslett; Pam M. Berry; Györgyi Bela; Rob H. G. Jongman; György Pataki; Michael J. Samways; Martin Zobel (Biodiversity and Conservation, 2010)

Identifying and prioritising services in European terrestrial and freshwater ecosystems - Paula A. Harrison; Marie Vandewalle; Martin T. Sykes; Pam M. Berry; Rob Bugter; Francesco de Bello; Christian K. Feld; Ulf Grandin; Richard Harrington; John R. Haslett; Rob H. G. Jongman; Gary W. Luck; et al. (Biodiversity and Conservation, 2010)

A novel species of mastrevirus (family Geminiviridae) isolated from Digitaria didactyla grass from Australia - Rob W. Briddon; Darren P. Martin; Betty E. Owor; Lara Donaldson; Peter G. Markham; Ray S. Greber; Arvind Varsani (Archives of Virology, 2010)

Identification of novel chromosomal regions associated with airway hyperresponsiveness in recombinant congenic strains of mice - Pierre Camateros; Rafael Marino; Anny Fortin; James G. Martin; Emil Skamene; Rob Sladek; Danuta Radzioch (Mammalian Genome, 2010)

A signaling-selective, nanomolar potent allosteric low molecular weight agonist for the human luteinizing hormone receptor - Chris J. van Koppen; Guido J. R. Zaman; C. Marco Timmers; Jan Kelder; Sietse Mosselman; Ruud van de Lagemaat; Martin J. Smit; Rob G. J. M. Hanssen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Changes in markers of muscle damage, inflammation and HSP70 after an Ironman triathlon race - Katsuhiko Suzuki; Jonathan Peake; Kazunori Nosaka; Mitsuharu Okutsu; Chris R. Abbiss; Rob Surriano; David Bishop; Marc J. Quod; Hamilton Lee; David T. Martin; Paul B. Laursen (European Journal of Applied Physiology, 2006)

Spatial relationships and matrilineal kinship in African savanna elephant (Loxodonta africana) clans - Russell A. Charif; Rob Roy Ramey; William R. Langbauer; Katharine B. Payne; Rowan B. Martin; Laura M. Brown (Behavioral Ecology and Sociobiology, 2005)

Role of transglutaminase1 in stabilisation of intercellular junctions of the vascular endothelium - Werner Baumgartner; Nikola Golenhofen; Agnes Weth; Takashi Hiiragi; Rob Saint; Martin Griffin; Detlev Drenckhahn (Histochemistry and Cell Biology, 2004)

Cycles and synchrony in the Collared Lemming (Dicrostonyx groenlandicus) in Arctic North America - Martin Predavec; Charles J. Krebs; Kjell Danell; Rob Hyndman (Oecologia, 2001)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)